EIB Global Report The Impact - European Investment Bank (2022)
"The European Investment Bank (EIB) has a long track record as a provider of development and climate finance, working with EU institutions, Member States and partner countries in the EU neighbourhood, sub-Saharan Africa and around the world to foster sustainable development and bring real benefits to people's lives. The challenges faced by our partners around the world are many: economies struggle to provide adequate jobs and basic infrastructure, while dealing with the growing needs for climate action and protection of the environment. These challenges have been aggravated by the coronavirus pandemic and the ramifications of the conflict in Ukraine. As of the start of 2022, the EIB's development finance role is being taken forward and intensified through EIB Global. The new structure builds on the strength and experience that the EIB has gained working outside Europe to mobilise more development and climate finance, and increase impact. The purpose of this report is twofold. First, it provides an overview of the Bank's activities outside the European Union in 2021, with a focus on the expected results, complemented by reporting on the results already achieved by past operations. Second, it elaborates on the context of the Bank's engagement in countries outside Europe, examining different development challenges and how they confront different regions, drawing on our own development research."